Teacher Competency in Using Image Media to Improve Children's Memory at RA A Miftahul Ulum Sana Daja Village, Pasean District, Pamekasan Regency - Fatimatuzzahrah; Dewi Pusparini; Musayyadah (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2024)
Learnig  media is very useful  to use in learning. The use of media in learning can make it easier and attract students' learning interest. This research aims to analyze teacher competence in using image media to improve children's memory at RA A Miftahul Ulum Sana Daja Pasean Pamekasan. This research use desciptive qualitative approach. The subjects in this research were the principal and class A teacher at RA Miftahul Ulum. Data collection used in this research was observation, interviews and documentation, data analysis was carried out by data condensation, data presentation and conclusions. The results of this research show that teacher competence in using image media to improve children's memory at RA A Miftahul Ulum is very good. This can be seen from how the teacher's ability to plan lessons using image media to improve children's memory runs smoothly and children are able to recall what they have learned using images.